MODEL AKUNTABILITAS KEUANGAN GEREJA TORAJA: STUDI INTERPRETIF FENOMENOLOGI - Ratu Resti; Fransiskus Randa; Oktavianus Pasoloran (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2021)
Financial accountability of religious organizations is a new phenomenon demanded by stakeholders. This study aims to reveal the financial accountability of a religious organization, namely the Toraja Church. Data were collected through in-depth interviews, observation and documentation. The object of this research is the Toraja Church of Imanuel Mandetek congregation and selects the pastor, treasurer, and verification division as key informants. The results of the study found that financial accountability in the Toraja JIM church was not fully realized. The meaning of financial accountability in the church is interpreted as a form of financial governance with the demand for the involvement of the congregation in realizing the vision of the organization, but on the other hand, financial accountability built by the principle of transparency is not sufficient. Transparency of financial budgets has not been implemented. The financial statement information submitted is still very simple and is not accompanied by an adequate budgeting process. Thus the accountability that is carried out has not been able to meet the expectations of the Church stakeholders as part of the services provided.